2007
DOI: 10.1080/03610730701761957
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age on Intestinal Dipeptidyl Peptidase IV (DPP IV/CD26), Disaccharidases, and Alkaline Phosphatase Enzyme Activity in C57BL/6 Mice

Abstract: The objective of this study was to determine and describe the age-related changes in intestinal brush border membrane enzyme activities that occur in C57Bl/6 mice. Specifically, jejunal, duodenal, and ileal dipeptidyl peptidase IV/CD26, disaccharidase (lactase, sucrase, and maltase), and alkaline phosphatase activities were determined. A significant correlation between analyzed intestinal brush border membrane enzyme activities and animal age was found. Our study revealed that intestinal dipeptidyl peptidase I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
(23 reference statements)
1
12
1
Order By: Relevance
“…They increase to adult values at the time of weaning, between 20 and 24 days of life, suggesting the influence of dietary changes at that period. AP activity all along the small intestine decreases by 50% in elderly rats and mice 21,22 …”
Section: Alkaline Phosphatases: Backgroundmentioning
confidence: 97%
See 2 more Smart Citations
“…They increase to adult values at the time of weaning, between 20 and 24 days of life, suggesting the influence of dietary changes at that period. AP activity all along the small intestine decreases by 50% in elderly rats and mice 21,22 …”
Section: Alkaline Phosphatases: Backgroundmentioning
confidence: 97%
“…In rodents, intestinal AP gene expression and enzyme activity remain low during the suckling period 20,21 . They increase to adult values at the time of weaning, between 20 and 24 days of life, suggesting the influence of dietary changes at that period.…”
Section: Alkaline Phosphatases: Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of PPA on Sucrase and Isomaltase Activities of SI-SI catalyzes the hydrolysis of sucrose and about 80% of dietary maltose, whereas maltase-glucoamylase (EC 3.2.1.20/3) catalyzes the hydrolysis of the remaining maltose (44,45). Maltose is produced when ␣-amylase breaks down starch (46).…”
Section: Effect Of Bbmv On Starch Degradation By Ppa-as Shown Inmentioning
confidence: 99%
“…In fact, at 42 days of age the activity is increasing toward its highest level and at 1 year it is decreasing toward its lowest level 13. Moreover, an early study showed that the adaptive response of the intestine is reduced in old age 27.…”
Section: Discussionmentioning
confidence: 99%